Microencapsulación del extracto de pulpa integral de sinamillo (Oenocarpus mapora H. karst) por Spray drying y su efecto en su contenido bioactivo - Shapiama Vásquez, Alfonso (2025)
This research study aimed to microencapsulate the whole pulp extract of sinamillo (Oenocarpus mapora H. karst.) using spray drying to obtain stable microparticles with a high content of bioactive compounds. For this purpose, gum arabic and inulin were used as encapsulating materials at a 10% concentration, evaluating their effect on the retention of total phenols, anthocyanins, and antioxidant capacity (DPPH). The optimization process was developed using MSR with a DCCR, considering the inlet temperature (120 to 145 °C) and the total concentration of the encapsulant (10%) as independent variables. The results showed that sinamillo fruits have a high content of fats, proteins, fiber, and carbohydrates, as well as a significant concentration of phenolic compounds and antioxidant activity, especially when in extract form. The microencapsulation of the sinamillo extract yielded microparticles with characteristic coloration, good stability, and high retention of phenolic compounds. Statistical analysis revealed that drying temperature had a significantly greater influence (p0.05). The optimal drying conditions were determined to be an inlet temperature of 126.25 °C, with a formulation of 0.75% gum arabic and 0.25% inulin. This resulted in microparticles with 102.78 mg GAE/g of total phenolics, 30.15 mg C-3-G/g of anthocyanins, and 3594.86 µmol TE/g of antioxidant capacity (DPPH).